Clinical evaluation for the pharyngeal oxygen saturation measurements in shocked patients - Eman Arafa Hassan; Sherouk Nasser Mohamed; Emad Hamdy Hamouda; Nadia Taha Ahmed (BMC, 2022)
Abstract Background Monitoring oxygen saturation in shocked patients is a challenging nursing procedure. Shock syndrome alters peripheral tissue perfusion and hinders peripheral capillary oxygen saturation (SpO2) measurements. Our study aimed to find a solution to this problem. The pharynx is expected to be an accurate SpO2 measurement site in shocked patients. We clinically evaluated the pharyngeal SpO2 measurements against the arterial oxygen saturation (SaO2) measurements. Methods A prospective cohort research design was used. This study included 168 adult shocked patients. They were admitted to five intensive care units from March to December 2020 in an Egyptian hospital. A wrap oximeter sensor was attached to the posterior surface of an oropharyngeal airway (OPA) by adhesive tape. The optical component of the sensor adhered to the pharyngeal surface after the OPA insertion. Simultaneous pharyngeal peripheral capillary oxygen saturation (SpO2) and arterial oxygen saturation (SaO2) measurements were recorded. The pharyngeal SpO2 was clinically evaluated. Also, variables associated with the SpO2 bias were evaluated for their association with the pharyngeal SpO2 bias. Results The pharyngeal SpO2 bias was − 0.44% with − 1.65 to 0.78% limits of agreement. The precision was 0.62, and the accuracy was 0.05. The sensitivity to detect mild and severe hypoxemia was 100%, while specificity to minimize false alarm of hypoxemia was 100% for mild hypoxemia and 99.4% for severe hypoxemia. None of the studied variables were significantly associated with the pharyngeal SpO2 bias. Conclusion The pharyngeal SpO2 has a clinically acceptable bias, which is less than 0.5% with high precision, which is less than 2%.